Biological and pre-clinical trial evaluation of a local medicinal plant bacopa monnieri (L.) Penn - Azad, Abul Kalam; Awang, Mohamed; Rahman, Md. Mokhlesur; Akter, Seikh Farid Uddin (Radiance Research Academy, Nagpur, MH, India, 2012)
This study work was carried out to investigate the pharmacological prooperlies of 'Bacopa monxieri'. This study reveals that the plant has antibacterial and antimutagenic activities. Thus an attempt was made to reinvestigate aforementioned anrimicrobial as well as cytotoxic properties for the bark constituents. Bacopa monnieri (L.) Penn., (root bark and stem bark) have been intended to be accomplished in this study. Review of the biological activities of Bacopa monnieri (L.) Penn. The powdered plant was successively extracted with ether solvent. The antimicrobial investigation showed activity against four bacteria and one fungus.